Implementation of Regional Regulation Number 6 of 2016 Against the Natural Stone Industry that Violates Waste Management Provisions - Didi Rosadi; Syafira Indasari Dewi; Sandy Meidianto; Ratu Mawar Kartina; Siska Karina (Pusat Publikasi Nusantara, 2025)
The natural stone industry in Cirebon Regency plays an important role in supporting local economic growth, but has the potential to cause environmental pollution due to suboptimal waste management. The Regional Government of Cirebon Regency has established Regional Regulation Number 6 of 2016 as the foundation for environmental management and protection. This study aims to evaluate the implementation of these regulations in the supervision and management of waste by natural stone industry players and examine the effectiveness of the role of local governments in its implementation. The method used is normative juridical with a qualitative approach through interviews, observations, and document studies. The results of the study show that there are still many industry players who dispose of waste directly into the environment without adequate treatment processes. Weakness in supervision, limited processing facilities, and low environmental awareness are the main causes. This study shows the need to improve the regional supervision system through cross-sector coordination, increasing the frequency of field inspections, and consistent enforcement of administrative sanctions. In addition, it is necessary to develop adaptive technical policies with a participatory approach, as well as improve communal WWTP so that waste management runs more effectively and equitably. This research also emphasizes the importance of building awareness of industry players through intensive socialization, community-based coaching, and encouraging the use of waste as an alternative raw material with economic value.